Ultrahigh-strength steel cord steel with excellent fatigue performance and production method thereof
By optimizing the chemical composition and production process of steel for ultra-high-strength steel cords, the problem of insufficient strength and fatigue performance of steel cords is solved, and ultra-high-strength steel cords with high sonitization rate are produced, achieving the effects of high strength, high toughness and excellent fatigue performance, which is suitable for the development of green tires.
Patent Information
- Application Number
- CN202510454969.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2025-08-08
AI Technical Summary
The prior art is difficult to simultaneously improve the strength and fatigue performance of steel cords, especially the fatigue performance of ultra-high strength steel cords, and cannot meet the development needs of green tires.
By optimizing the chemical composition and production process of steel for steel cords, including electric furnace smelting, LF refining, RH vacuum degassing, billet continuous casting, diffusion annealing and high-line controlled rolling, chemical composition and process parameters are controlled to ensure that the sonitization rate reaches more than 95%, the tensile strength of hot-rolled state Rm≥1270MPa, the same-circle difference is ≤65MPa, and the cross-section shrinkage rate Z≥42%. The three-stage cooling method is used to control the tissue transformation to produce ultra-high-strength steel cords with high sonitization rate.
The tensile strength of the steel wire is ≥4000MPa, 360° twist ≥22 times, good torsion fracture, high strength, high toughness and excellent fatigue performance, and the fatigue life of the coil is ≥1.5 million times, which is suitable for large-scale industrial production.
Smart Images

Figure CN120443061A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ultra-high strength steel cord steel, and in particular relates to ultra-high strength steel cord steel with excellent fatigue performance and a production method thereof. Background Art
[0002] In recent years, with the explosive growth of my country's automotive industry, the tire industry has experienced rapid development. Tire production and quality are indicators of a country's automotive industry development level. Radial tires offer superior safety, high speed, fuel efficiency, and driving performance, and are the future direction of tire development. Steel cord is widely used in radial tire production due to its high strength, excellent wear resistance, rapid heat dissipation, and excellent elasticity. As one of the primary raw materials for tire carcasses, it is known as the "crown" of wire products.
[0003] In line with the requirements of the national dual-carbon policy, the concepts of low-carbon economy and energy conservation and emission reduction are gaining popularity. Green and environmentally friendly vehicles have become an inevitable trend in the development of the automotive industry. Correspondingly, automobile tires are developing towards lightweighting. This has led to increasing requirements for the safety, comfort, and economy of radial tires. The development of steel cord towards higher strength, higher thermal conductivity, and longer fatigue life has become a major trend in radial tires to adapt to the development of green tires. The mainstream steel cord in the market is gradually transitioning from high-strength steel cord (HT) to ultra-high-strength steel cord (ST) and ultra-high-strength steel cord (UT).
[0004] At present, the main way to improve the strength level of steel cord is to increase the carbon content. However, as the carbon content increases, the fatigue of the steel wire continues to decrease. Therefore, the development of steel cords with higher strength and good fatigue performance will become the future development trend of the steel cord industry.
[0005] Chinese patent CN114182164A discloses a steel for steel cord with a tensile strength of ≥4000MPa and a production method, relating to the technical field of steel production. The steel has the following chemical composition and weight percentages: C: 0.89-1.10wt%, Si: 0.10-0.30wt%, Mn: 0.20-0.60wt%, P≤0.015wt%, S≤0.010wt%, Cr: 0.01-0.40wt%, Ni: 0.01-0.20wt%, Cu: 0.005-0.30wt%, Al≤0.0020wt%, Ti≤0.0016wt%, N≤0.0070wt%, and the rest is Fe and unavoidable impurities. The wire rod is mainly composed of troostite structure, which avoids the formation of network cementite that affects drawing. The final tensile strength of the finished steel cord is above 4000MPa, which meets the requirements of energy conservation and environmental protection and the continuous improvement of the strength of steel cord for lightweight automobile tires, but cannot meet the requirements of high fatigue performance.
[0006] Chinese patent CN110629132A discloses a wire rod for ultra-high-strength steel cord and a manufacturing method thereof. The manufacturing method comprises the following steps: a steelmaking stage, in which molten steel having an inclusion density of ≤0.5 pieces / mm2 and an inclusion size of ≤30 μm and a steel bar size of ≥5 μm is smelted; a billet casting stage, in which the tapped steel from the steelmaking stage is cast into a billet having a central carbon segregation value of 0.92 to 1.08; a billet opening stage, in which the billet is opened into an intermediate billet having a central carbon segregation value of 0.95 to 1.05; a rolling stage, in which the intermediate billet is rolled into the wire rod; and a controlled cooling stage, in which the wire rod is temperature-controlled and cooled to obtain a wire rod having high cleanliness, high homogeneity, and a tensile strength of ≤1150 MPa. The wire rod can be used for ultra-high-strength steel cord with a single-filament tensile strength of ≥3600 MPa, and can ensure low wire breakage rate during drawing, wire breakage rate during stranding, and die loss, and a high yield rate. This patent can only meet the production of high-strength steel cord at the 3600MPa level, and cannot meet the production of higher-level steel. Summary of the Invention
[0007] In order to solve the above technical problems, the present invention provides an ultra-high strength steel cord steel with excellent fatigue performance and a production method thereof, wherein the steel cord steel has a sorbitization rate of more than 95% and a hot-rolled tensile strength R m ≥1270MPa, with a circle difference of ≤65MPa and a cross-sectional reduction rate Z of ≥42%. The steel wire produced by this method has a tensile strength of ≥4000MPa and high fatigue resistance. Its production process is stable and reliable, suitable for large-scale industrial production.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] The present invention provides an ultra-high-strength steel for steel cord with excellent fatigue performance. The chemical composition and weight percentage of the steel cord steel are as follows: C 0.90-0.98%, Mn 0.15-0.30%, Cr 0.05-0.10%, Si 0.25-0.35%, V 0.015-0.025%, Nb 0.015-0.025%, Alt≤0.001%, Ti≤0.0005%, P≤0.010%, S≤0.010%, O≤0.0020%, N≤0.0065%, and the remainder is Fe and unavoidable impurity elements; wherein 1.5≤A=13*Cr+25*V+28*Nb≤2.5, and in the calculation formula of A, the value of each component is its content in the steel×100.
[0010] The hot-rolled microstructure of the steel cord steel is sorbite, the sorbite ratio is ≥95%, and the grain size is ≥9.0.
[0011] The hot-rolled tensile strength R of the steel cord steel m ≥1270MPa, same-circle difference ≤65MPa, section reduction rate Z ≥42%; ultra-high cycle fatigue test is carried out under load conditions of 600-800MPa, and the fatigue life of wire rod is ≥1.5 million times.
[0012] The non-metallic inclusions of hot-rolled steel cord steel are Class B and Class D ≤ 0.5 level, Class A and Class C ≤ 1.5 level, the maximum size of inclusions (longitudinal width, transverse size) ≤ 25 μm, the maximum width of titanium inclusions ≤ 5 μm, and the number of inclusions is < 1000 / cm 2 , there are no pure Al2O3 inclusions.
[0013] The steel wire made of the steel used for the steel cord has a tensile strength of ≥4000 MPa, can be twisted 360° ≥22 times, has a good torsional fracture, has high strength and high toughness, and also has excellent fatigue performance.
[0014] The present invention also provides a production method for the ultra-high strength steel cord steel with excellent fatigue performance, which comprises the following steps: electric furnace smelting → LF refining → RH vacuum degassing → billet continuous casting → diffusion annealing → high-strength wire controlled rolling → controlled cooling.
[0015] In the electric furnace smelting step, the endpoint C is controlled at ≤0.10%, P≤0.0080%, and S≤0.08%. The steel is tapped with slag blocking, and refined slag and lime are added when about 1 / 5 of the molten steel is tapped. When about 1 / 3 of the molten steel is tapped, a deoxidizer and an alloy are added in the following order: silicon balls → slag → silicon manganese → high carbon ferrochrome → recarburizer. A low-Al alloy is used to strictly prevent Al from being introduced into the alloy.
[0016] In the LF furnace refining step, argon is blown from the bottom of the ladle throughout the entire process, and the argon flow rate is based on the requirement that the molten steel does not splash out of the ladle; in order to avoid the formation of large brittle Al2O3-type hard inclusions in the steel, a Si deoxidation process is adopted, and a silicon ball deoxidizer is selected as a deoxidizer. In order to modify the inclusions and make them deformable inclusions to prevent brittle fracture of the steel wire during drawing, lime and wollastonite are added to form slag, with basicity (CaO / SiO2) ≤1.0, Al2O3 ≤5%, Als in the steel ≤5ppm, and a large Ar gas flow rate is used for stirring as much as possible without exposing the slag surface; sufficient silicon carbide is added to the slag; the FeO content of the slag is controlled between 2 and 3%; argon is blown from the bottom of the ladle throughout the entire process, and the argon flow rate is based on the requirement that the molten steel does not splash out of the ladle; the use of Al-containing alloys is strictly controlled, the white slag time is ≥20 minutes, and alloys are added before and during refining to adjust the Si, Mn, Cr, V, and B contents based on the component analysis results before entering the LF furnace.
[0017] During the RH vacuum degassing step: in the early vacuum stage, if the vacuum degree is ≤100 Pa, the vacuum holding time is ≥10 minutes; if the vacuum degree is ≤200 Pa, the vacuum holding time is ≥15 minutes; in the late vacuum stage, the vacuum holding time is ≥10 minutes. Based on the composition analysis results of the early vacuum stage, if composition adjustment is required in the mid-term, the vacuum holding time must be maintained for more than 5 minutes after the adjustment. A soft argon purge treatment is performed before leaving the station, with a soft purge time of ≥15 minutes. Based on the composition analysis results at the RH endpoint, alloys are added to adjust the V, Ti, B, and Ni contents.
[0018] To obtain low-segregation ingots, the continuous casting process uses large square billets, and the casting process is fully protected. Electric stirring in the mold and electric stirring at the end of the mold plus soft reduction are used. The mold electromagnetic stirring frequency is 3.0 Hz, the current is 400A, the end electromagnetic stirring frequency is 4.0 Hz, the current is 800A, the reduction is 10 mm, the superheat is controlled at 20-40°C, and the casting speed is 0.40-0.55 mm / min. Low-segregation, defect-free ingots are obtained. The large square billets have a size of 380 mm by 450 mm.
[0019] In the diffusion annealing step, in order to further improve segregation, high-temperature diffusion annealing is used for billet rolling, with a soaking zone temperature of 1200-1300°C and a holding time of ≥10h to improve the segregation of the cast billet, with the carbon segregation index of the cast billet ≤1.10.
[0020] In the high-speed wire controlled rolling step, the starting rolling temperature is 950-1000°C, the finishing rolling temperature is 810-840°C, the sizing temperature is 870-910°C, and the spinning temperature is 890-930°C.
[0021] In the controlled cooling step, a three-stage cooling method is adopted, wherein the first stage has a cooling rate of 7 to 11°C / s, cooling to 600 to 650°C; the second stage has a cooling rate of 7 to 9°C / s, cooling to 500 to 550°C; and the third stage has a cooling rate of ≤3°C / s, cooling to 300 to 400°C.
[0022] The present invention also provides a steel cord prepared using the steel for ultra-high strength steel cord with excellent fatigue performance according to the present invention.
[0023] The preparation method of the steel cord is: peeling or pickling → rough drawing Specifications → Heating → Pickling → Water Bath → Electroplating → Wet Drawing Specifications → Twisted strands.
[0024] Furthermore, the rough drawing is performed 13 times.
[0025] The functions and controls of the various components in the steel cord steel provided by the present invention are as follows:
[0026] C: The carbon element is essential for achieving high strength and hardness. To achieve the high strength required for high-strength steel cord, the carbon content must be above 0.90%. However, excessive carbon content increases carbon segregation, which can lead to the formation of abnormal structures such as central martensite and network cementite, impairing drawing performance. Furthermore, as the carbon content increases, thermal conductivity decreases, the critical drawing strain of the steel wire gradually decreases, and the material's drawing performance also gradually declines. Therefore, the carbon content should be controlled between 0.90 and 0.98%.
[0027] Si: As a solid solution hardening element, Si can significantly increase the strength of high carbon steel. Increasing the Si content in high carbon steel wire rods helps reduce the segregation of carbon atoms in the ferrite lamellae, reducing the formation of central martensite and network cementite. Si can also significantly delay the exothermic peak of the steel wire to a higher temperature range, thereby improving the thermal stability of the steel wire. Therefore, the Si content should be controlled at 0.25-0.35%.
[0028] Mn: Mn is an effective element for deoxidation and desulfurization, and can also improve the hardenability and strength of steel. However, if the Mn content is too high, it can easily cause segregation, resulting in the formation of harmful structures such as central martensite and network cementite, which deteriorates the toughness of the steel. Therefore, the Mn content is controlled within 0.15-0.30%.
[0029] Cr: It is a strong carbide-forming element and exists in the cementite lamellae to form alloy cementite, which can effectively inhibit the precipitation of the proeutectoid phase, increase the sorbitization rate, and achieve high strength and high toughness of the material; at the same time, the addition of Cr shifts the continuous cooling transformation curve of the steel to the right, thereby refining the interlamellar spacing. At the same time, Cr can also reduce the activity of C, which can reduce the decarburization tendency of the steel surface during heating, rolling and heat treatment, and is used to obtain high fatigue resistance. In addition, increasing the Cr content can inhibit the dissolution of cementite during drawing, reduce the amount of cementite dissolved, and thus improve the torsional stratification of the steel wire, so the Cr content is controlled at 0.05-0.10%.
[0030] V: The V element can significantly refine the grain size, which not only increases the strength and toughness of steel but also improves its low-temperature performance. Furthermore, V is a strong carbide-forming element. Its precipitation at the austenite grain boundaries during the initial phase transformation can reduce the grain boundary carbon content, effectively inhibiting the formation of network cementite. Furthermore, V (C, N) precipitated in ferrite can act as precipitation strengthening. Furthermore, due to the finer grains, corrosion resistance can also be improved. Excessively high V content results in higher costs. The V content can be controlled within the range of 0.015-0.025%.
[0031] Nb: Nb significantly refines grains, which not only increases the strength and toughness of steel but also improves its low-temperature properties. Nb is also a strong carbide-forming element. Its precipitation at austenite grain boundaries during the initial phase transformation can reduce the carbon content at the grain boundaries, effectively inhibiting the formation of network cementite. Furthermore, Nb (C, N) precipitated in ferrite can act as precipitation strengthening. Furthermore, due to the finer grains, it can also improve corrosion resistance. Excessive V content increases costs, so the Nb content can be controlled within the range of 0.015-0.025%.
[0032] Alt: As a strong deoxidizing element, Alt easily forms immutable Al2O3-type brittle inclusions with oxygen. Higher Alt content leads to larger and more brittle inclusions. Larger brittle inclusions, in particular, can cause drawing fractures, impacting serviceability, and significantly reducing fatigue life. Steel cord drawn wire is very fine, so to control inclusion morphology and size, the Alt content is strictly controlled to ≤0.001%.
[0033] Ti: Ti and N, impurities present in molten steel during solidification, accumulate in the interdendritic space due to solidification segregation, resulting in the precipitation of TiN inclusions. TiN inclusions are brittle, non-deformable inclusions with very high hardness, often appearing as triangles, rhombuses, or squares. They pose a serious threat to the fatigue and processing properties of steel materials and are the most direct cause of wire rod breakage during drawing or stranding. Unlike oxide inclusions, TiN inclusions cannot be plasticized through process technology, so their precipitation can only be controlled by strictly controlling their content. Therefore, the Ti content should be ≤ 0.0005%.
[0034] S and P: Impurity elements such as S and P segregate at grain boundaries, significantly reducing delayed fracture resistance. P can form microsegregations during solidification and subsequently segregate at grain boundaries during austenitization, significantly increasing the steel's brittleness and delayed fracture sensitivity. S forms MnS inclusions and segregates at grain boundaries, further increasing the steel's delayed fracture sensitivity. Therefore, the P and S contents should be controlled within the range of P ≤ 0.010% and S ≤ 0.010%.
[0035] Oxygen and nitrogen: Oxygen forms various oxide inclusions in steel. Under stress, these inclusions easily cause stress concentration, leading to the initiation of microcracks and deteriorating the steel's mechanical properties, especially toughness and fatigue resistance. Therefore, measures must be taken in metallurgical production to minimize its content, controlling it to 0.0020% or less. Nitrogen precipitates as Fe₄N in steel, which diffuses slowly, causing aging. Nitrogen also reduces the steel's cold working properties, so the nitrogen content should be controlled to 0.0065% or less.
[0036] In order to improve fatigue performance, V and Nb microalloying is adopted, and the Cr content is reduced at the same time, and the chemical composition satisfies 1.5≤13*Cr+25*V+28*Nb≤2.5. On the one hand, the fine and dispersed V and Nb carbides play a pinning role on grain boundary migration, hindering the growth of grains, which can effectively refine the size of pearlite clusters and obtain ultrafine grain structure with grain size ≥9.0. At the same time, it can increase the nucleation driving force of cementite, so that cementite particles are formed at different positions of grain boundaries, reduce the continuity of network cementite, eliminate network cementite, and improve fatigue performance. On the other hand, reducing the Cr content reduces the center segregation of the ingot, reduces the risk of martensite formation, and improves fatigue performance.
[0037] The production method of steel for steel cord provided by the present invention adopts a "two-fire material forming" process to obtain high-quality, low-inclusion ingots with a carbon segregation index of ≤1.10 through control of the smelting process; in order to further improve the segregation of the ingots and avoid the occurrence of abnormal structures such as central martensite and network cementite during wire rod rolling, the ingots are subjected to high-temperature diffusion annealing, the target temperature of the soaking section is 1200-1300°C, and the holding time of the soaking section is ≥10h.
[0038] To achieve ultra-high strength, the rolling process adopts a low finishing temperature + high spinning temperature method. The starting rolling temperature of the high-speed wire rolling is 950-1000°C. The present invention adopts an appropriate low-temperature rolling method, and the finishing temperature is controlled at 810-840°C, which is conducive to grain refinement, thereby improving the tensile strength of the wire rod. The sizing temperature and spinning temperature are relatively high, 870-910°C for sizing and 890-930°C for spinning, providing conditions for subsequent controlled cooling, ensuring an increased cooling rate at a relatively high spinning temperature, obtaining a large degree of undercooling, and thereby reducing the spacing between the sorbite lamellae and improving the tensile strength of the wire rod.
[0039] To achieve a high sorbitization rate, a three-stage cooling method is used. In the first stage, the fan is turned on at 100%, and the cooling rate is 7-11°C / s, cooling to 600-650°C. This rapid cooling produces a microstructure with fine lamellar spacing and a high sorbitization rate. The second stage undergoes isothermal phase transformation at a cooling rate of 7-9°C / s and the fan is turned on at 50-80%, cooling to 500-550°C. The third stage reduces the cooling rate and cools slowly to avoid the formation of central martensite structure, with a cooling rate of ≤3°C / s, cooling to 300-400°C. This three-stage cooling method effectively controls the transformation rate from the austenite region to the phase transformation point and throughout the entire phase transformation range, resulting in a smooth phase transformation process and increased phase transformation time. This helps increase the sorbite content of the wire rod and reduce the formation of abnormal structures. It also helps control the final cooling temperature and rate, reducing or eliminating the formation of abnormal structures.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The steel cord steel provided by the present invention has a sorbitization rate of more than 95%, a grain size of ≥9.0, a sorbitan interlamellar spacing of ≤130nm, and no central martensite or network cementite. m ≥1270MPa, same-turn difference ≤65MPa, cross-sectional shrinkage Z ≥42%, steel wire tensile strength ≥4000MPa, 360° torsion ≥22 times, good torsion fracture, high strength, high toughness, and excellent fatigue performance. Ultra-high cycle fatigue test under load of 600-800MPa, wire rod fatigue life ≥1.5 million times. Non-metallic inclusions of type B and type D ≤0.5 level, type A and type C ≤1.5 level, maximum size of inclusions (longitudinal width, transverse size) ≤25μm, maximum width of titanium inclusions ≤5μm, number of inclusions <1000 / cm 2 , without pure Al2O3 inclusions. Its production process is stable and reliable, suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is the metallographic structure diagram of the steel cord steel in Example 2;
[0043] Figure 2 is the grain size diagram of the steel cord steel in Example 3;
[0044] Figure 3 This is a macroscopic microstructure diagram of the steel cord steel slab in Example 4. DETAILED DESCRIPTION
[0045] The present invention provides an ultra-high strength steel cord steel with excellent fatigue performance. The chemical composition and weight percentage of the ultra-high strength steel cord steel are as follows: C 0.90-0.98%, Mn 0.15-0.30%, Cr 0.05-0.10%, Si 0.25-0.35%, V 0.015-0.025%, Nb 0.015-0.025%, Alt≤0.001%, Ti≤0.0005%, P≤0.010%, S≤0.010%, O≤0.0020%, N≤0.0065%, and the remainder is Fe and unavoidable impurity elements; wherein 1.5≤A=13*Cr+25*V+28*Nb≤2.5.
[0046] The production method of the ultra-high strength steel cord steel with excellent fatigue performance comprises the following steps: electric furnace smelting→LF refining→RH vacuum degassing→bill continuous casting→diffusion annealing→high-strength wire controlled rolling→controlled cooling.
[0047] During the electric furnace smelting process: the end point C is controlled at ≤0.10%, P≤0.0080%, and S≤0.08%; slag is blocked for tapping, and refined slag and lime are added when about 1 / 5 of the molten steel is tapped. When about 1 / 3 of the molten steel is tapped, deoxidizer and alloy are added in the following order: silicon balls → slag → silicon manganese → high carbon ferrochrome → recarburizer. Low Alt alloy is used to strictly prevent Al from being brought into the alloy.
[0048] During the LF furnace refining step: argon is blown from the bottom of the ladle throughout the entire process, and the argon flow rate is such that the molten steel does not splash out of the ladle; in order to avoid the formation of large brittle Al2O3-type hard inclusions in the steel, a Si deoxidation process is adopted, and a silicon ball deoxidizer is selected as the deoxidizer. In order to modify the inclusions and make them deformable inclusions to prevent brittle fracture during wire drawing, lime and wollastonite are added to form slag, with basicity (CaO / SiO2) ≤ 1.0, Al2O3 ≤ 5%, Als in the steel ≤ 5ppm, and a large Ar gas flow rate is used for stirring as much as possible without exposing the slag surface; sufficient silicon carbide is added to the slag; the FeO content in the slag is controlled between 2 and 3%; argon is blown from the bottom of the ladle throughout the entire process, and the argon flow rate is such that the molten steel does not splash out of the ladle; the use of Al-containing alloys is strictly controlled, and the white slag time is ≥ 20 minutes. According to the composition analysis results before entering the LF furnace, alloys are added before and during refining to adjust the Si, Mn, Cr, V, and B contents.
[0049] During the RH vacuum degassing step: In the initial vacuum stage, if the vacuum degree is ≤100 Pa, the vacuum hold time must be ≥10 minutes; if the vacuum degree is ≤200 Pa, the vacuum hold time must be ≥15 minutes; in the final vacuum stage, the hold time must be ≥10 minutes. Based on the composition analysis results of the initial vacuum stage, if composition adjustment is required during the intermediate stage, the vacuum hold time must be maintained for at least 5 minutes after the adjustment. Before leaving the station, soft argon purge treatment must be performed for ≥15 minutes. Alloying is then added to adjust the V, Ti, B, and Ni contents based on the composition analysis results at the RH endpoint.
[0050] In the continuous casting step of 380mm*450mm large square billets: in order to obtain low-segregation billets, large square billets are used for continuous casting, and the casting process is protected. Electric stirring of the crystallizer and electric stirring at the end + light pressure are used. The crystallizer electromagnetic stirring frequency is 3.0Hz, the current is 400A, the end electromagnetic stirring frequency is 4.0Hz, the current is 800A, the pressure reduction is 10mm, the superheat is controlled at 20-40℃, and the pulling speed is 0.40-0.55mm / min to obtain low-segregation and defect-free billets.
[0051] In the diffusion annealing step, the soaking zone temperature is 1200-1300°C, and the soaking zone holding time is ≥10h.
[0052] In the high-speed wire controlled rolling step, the starting rolling temperature is 950-1000°C, the finishing rolling temperature is 810-840°C, the sizing temperature is 870-910°C, and the spinning temperature is 890-930°C.
[0053] In the controlled cooling step, a three-stage cooling method is adopted, wherein the first stage has a cooling rate of 7 to 11°C / s, cooling to 600 to 650°C; the second stage has a cooling rate of 7 to 9°C / s, cooling to 500 to 550°C; and the third stage has a cooling rate of ≤3°C / s, cooling to 300 to 400°C.
[0054] The present invention is described in detail below with reference to the embodiments.
[0055] The chemical composition and weight percentage of the steel for steel cord in each embodiment and comparative example are shown in Table 1, with the remainder being iron and unavoidable impurities.
[0056] Table 1 Chemical composition (wt%)
[0057]
[0058] The production method of the steel cord steel in each embodiment and comparative example is as follows: electric furnace smelting→LF refining→RH vacuum degassing→bill continuous casting→diffusion annealing→high-speed wire controlled rolling→controlled cooling.
[0059] Some of the main process parameters are shown in Table 2. The chemical composition of Comparative Example 3 is the same as that of Example 4.
[0060] Table 2
[0061]
[0062]
[0063] The microstructure of the hot-rolled wire rod produced by the above process is shown in Table 3, the inclusion rating is shown in Table 4, and the performance is shown in Table 5.
[0064] Table 3
[0065]
[0066] Table 4 Rating of non-metallic tight inclusions in hot-rolled wire rod
[0067]
[0068] Table 5 Mechanical properties of hot rolled wire rod
[0069]
[0070] The hot rolled wire rods in the above embodiments and comparative examples are prepared into steel wires according to the following steps: peeling or pickling → rough drawing Specifications → 1100℃ heating → pickling → water bath → electroplating → 40℃ wet drawing Specification.
[0071] Table 6
[0072]
[0073]
[0074] From the above, it can be seen that the solution provided by the present invention can produce a tensile strength R m ≥1270MPa, same-turn difference ≤65MPa, cross-sectional reduction rate Z ≥42%, ultra-high cycle fatigue test under load of 600-800MPa, wire rod fatigue life ≥1.5 million times of hot-rolled wire rod; after this wire rod is made into steel wire, the tensile strength of the steel wire is ≥4000MPa, 360° torsion ≥22 times, and the torsional fracture is good. It has high strength, high toughness, and excellent fatigue performance.
[0075] In Comparative Example 1, since V and Nb were not added, the strength was insufficient.
[0076] In Comparative Example 2, although the contents of the chemical components meet the requirements of the present invention, the A value does not meet the requirements of the present invention, resulting in insufficient toughness.
[0077] In Comparative Example 3, due to inappropriate control of the cooling rate in the cooling step, the wire rod has insufficient plasticity and toughness.
[0078] The above-mentioned detailed description of an ultra-high strength steel cord steel with excellent fatigue performance and its production method with reference to the embodiments is illustrative rather than restrictive. Several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. An ultra-high strength steel cord steel with excellent fatigue performance, characterized in that: The chemical composition and weight percentage of the steel for steel cord are: C 0.90-0.98%, Mn 0.15-0.30%, Cr 0.05-0.10%, Si 0.25-0.35%, V 0.015-0.025%, Nb 0.015-0.025%, Alt≤0.001%, Ti≤0.0005%, P≤0.010%, S≤0.010%, O≤0.0020%, N≤0.0065%, and the rest are Fe and unavoidable impurity elements; wherein, 1.5≤A=13*Cr+25*V+28*Nb≤2.
5.
2. The ultra-high strength steel cord steel with excellent fatigue performance according to claim 1, characterized in that: The hot-rolled microstructure of the steel cord steel is sorbite, the sorbite ratio is ≥95%, and the grain size is ≥9.
0.
3. The ultra-high strength steel cord steel with excellent fatigue performance according to claim 1, characterized in that: The hot-rolled tensile strength R of the steel cord steel m ≥1270MPa, same-circle difference ≤65MPa, section reduction rate Z ≥42%; ultra-high cycle fatigue test is carried out under load conditions of 600-800MPa, and the fatigue life of wire rod is ≥1.5 million times.
4. The ultra-high strength steel cord steel with excellent fatigue performance according to claim 1, characterized in that: The steel cord is made of steel with a tensile strength of ≥4000 MPa and a 360° torsion of ≥22 times.
5. The method for producing ultra-high strength steel cord steel with excellent fatigue performance according to any one of claims 1 to 4, characterized in that: The production method comprises the following steps: electric furnace smelting→LF refining→RH vacuum degassing→bill continuous casting→diffusion annealing→high-speed wire controlled rolling→controlled cooling.
6. The production method according to claim 5, characterized in that In the diffusion annealing step, the soaking zone temperature is 1200-1300° C., and the soaking zone holding time is ≥10 h.
7. The production method according to claim 5, characterized in that In the high-speed wire controlled rolling step, the starting rolling temperature is 950-1000°C, the finishing rolling temperature is 810-840°C, the sizing temperature is 870-910°C, and the spinning temperature is 890-930°C.
8. The production method according to claim 5, characterized in that In the controlled cooling step, a three-stage cooling method is adopted, wherein the first stage cooling rate is 7-11°C / s, cooling to 600-650°C; the second stage cooling rate is 7-9°C / s, cooling to 500-550°C; and the third stage cooling rate is ≤3°C / s, cooling to 300-400°C.
9. A steel cord prepared using the steel for ultra-high strength steel cord with excellent fatigue performance according to any one of claims 1 to 4.
10. The method for producing a steel cord according to claim 9, wherein: The production method comprises the following steps: peeling or pickling → rough drawing to a specification of φ1.0-2.0 mm → heating → pickling → water bath → electroplating → wet drawing to a specification of φ0.1-0.2 mm → stranding.
Citation Information
Patent Citations
Wire rod used for ultrahigh-strength steel cord and manufacture method of wire rod
CN110629132A
Steel for steel cord with tensile strength larger than or equal to 4000 MPa and production method
CN114182164A
Cited By
High-strength high-cycle-ratio steel cord and green manufacturing process
CN121380775A
High strength high cycle ratio steel cord and green manufacturing process
CN121380775B